Assessing Structural Adjustment and Economic Reform: The Case of New Zealand - Hall, Viv (School of Management Working Papers, 1998)
Against the background of a set of macroeconomic and microeconomic problems which were diagnosed as more deepset and wide-ranging than for other developed economies, New Zealand has experienced more than a decade of significant economic reform and structural change. During this time, many other countries have been reforming and adapting to varying degrees. New Zealand has made very significant progress over the 1984-1997 time period in most key macroeconomic and many microeconomic areas, but still faces major challenges of sustainability and improvement on almost all fronts. The need for the latter is due variously to the relative ease with which macroeconomic imbalances can re-emerge under lax policy settings, the still relatively inconclusive evidence on the sustainability of improved economic and productivity growth performance, a widespread desire to reduce the NAIRU further, and the likelihood that in recent years other countries’ reforms have eroded a number of the comparative advantages New Zealand had achieved in key areas. In the absence of a further major crisis, another ’big bang’ sequence of reforms seems unlikely, especially under New Zealand’s current MMP electoral system. But the international and domestic economic evidence is certainly consistent with considerable ongoing adjustment being required.